Layanan Makanan dan Minuman di Hotel Amaris Diponegoro Yogyakarta - Erlin Estiana Yuanti; Lidia Citra Luckyrainita (Jurnal Pariwisata Terapan, 2017)
The purpose of the research is to explain about the profile of food and beverage department in Amaris Hotel Diponegoro Jogja. In addition, the services provided by F & B department will also be discussed along with the challenges faced by the staff in F & B department. The methods used in this research consist of field study and library study. The field study was done in the form of direct observation and some interviews. Besides, the library study was also conducted to gaininformation from books, e-book, internet sources, and the handout obtained from Amaris Hotel Diponegoro Jogja including information on its human resources and the food and beverage department databases.Based on the finding obtained from the research, Amaris Hotel Diponegoro Jogja offers the basic standard facilities to the guests, namely bed and breakfast. The breakfast service was handled by the food and beverage department. In addition to the breakfast service, the food and beverage department also serves welcome drink service, meeting and banquet service, table service, and room service. The research also obtains several challenges faced by the staff in the food and beverage department, such as the time management, the communication among the kitchen staffs and the guests. To solve the challenges respectively, some ways were applied by the F & B staff, such as sharing jobs, holding intensive briefings, and also paying attention to the guests’ requests and giving service to the guests according to their requests.